Radiation doses from low-dose CT scans in SPECT/CT and PET/CT examinations: A survey in Germany - Rinscheid, Andreas; Janzen, Tilman; Alikhani, Babak; Beer, Ambros J.; Braune, Anja; Eberhardt, Nina; Fechner, Diana; Förster, Stefan; Freesmeyer, Martin; Furth, Christian; Grunert, Michael; Hellwig, Dirk; Costa, Pedro Fragoso; Kühnel, Christian; Lange, Catharina; Linke, Rainer; Razlaw, Natalia; Sack, Tobias; Schmidt, Daniel; Schütze, Christina; Starke, Alexander; Tondera, Liane; Wengenmair, Hermann; Zöphel, Klaus; Burchert, Wolfgang; Lapa, Constantin (Nuklearmedizin - NuclearMedicine, 2022)
Aim Recently, dose reference levels (DRLs) have been defined in Germany for auxiliary low-dose CT scans in hybrid SPECT/CT and PET/CT examinations, based on data from 2016/17. Here, another survey from 2020 was evaluated and compared with the new DRLs as well as with similar surveys from foreign countries.Methods The survey, which had already been conducted in the Nordic countries, queried for various examinations including the following values: patient weight and height, volume CT dose index (CTDIvol), dose length product (DLP). For each examination, statistical parameters such as the third quartile (Q3) were determined from all submitted CTDIvol and DLP values. Additionally, for examinations comprising datasets from at least 10 systems, the third quartile (Q3-Med) of the respective median values of each system was calculated. Q3 and Q3-Med were compared with the newly published DRLs from Germany and values from similar studies from other countries.Results Data from 15 SPECT/CT and 13 PET/CT systems from 15 nuclear medicine departments were collected. For the following examinations datasets from more than 10 systems were submitted: SPECT lung VQ, SPECT bone, SPECT&PET cardiac, PET brain, PET oncology. Especially for examinations of the thorax and heart, the new DRLs are very strict compared to this study. The CTDIvol values for examinations of the head were lower in this study than the DRLs prescribe now.Conclusions For certain examination types, there is a need for dose optimization at some clinics and devices in order to take into account the new DRLs in Germany in the future.
Keywords: Hybride Bildgebung; CTDI; DLP; Dosisreferenzwerte (DRW)